2015
DOI: 10.1136/bjophthalmol-2014-306248
|View full text |Cite
|
Sign up to set email alerts
|

Association between penetrating eye injuries and attention deficit hyperactivity disorder in children

Abstract: There was an association between penetrating eye injuries and inattentiveness, hyperactivity, oppositional defiant disorder and conduct disorder in boys, and conduct disorder in girls. An appropriate evaluation of ADHD symptoms may prevent vision loss due to penetrating eye injuries in children. In addition, evaluation by a child psychiatrist of children presenting with penetrating eye injuries may prevent repetition of injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Children ≤ 5 years are at a particularly high risk for exposure to potentially traumatic events due to their dependence on caregivers. Negligence of the guardian and some behavioural conditions like attention defi cit hyperactivity disorder are added risk factors (Bayar et al, 2015). In children, apart from the clinical signs and symptoms being diff erent from that in adults, they also do not complain of pain or visual problems and hence risk delay in seeing a doctor.…”
Section: Introductionmentioning
confidence: 99%
“…Children ≤ 5 years are at a particularly high risk for exposure to potentially traumatic events due to their dependence on caregivers. Negligence of the guardian and some behavioural conditions like attention defi cit hyperactivity disorder are added risk factors (Bayar et al, 2015). In children, apart from the clinical signs and symptoms being diff erent from that in adults, they also do not complain of pain or visual problems and hence risk delay in seeing a doctor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown an association with ADHD symptoms in various injury types including poisonings, extremity fractures, traumatic dental injuries, eye injuries, burn injuries and ear and nose foreign body insertions. The findings of those studies have concluded that children and adolescents with ADHD are more prone to injury and trauma compared to healthy peers [17][18][19][20][21][22][23]. Many studies have reported that ADHD can develop after head trauma [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies highlight the relationship between ADHD and trauma incidents in pediatric population. [ 14 15 16 17 18 ] On the other hand, in the literature, there are relatively limited reports on the relationship between ADHD and trauma in adults. Kaya et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, only two studies carried out on the relationship between penetrating eye traumas and ADHD in children can be found. [ 15 22 ] The significant association found in their studies gives rise to consider the negative impact of ADHD on the ocular traumas in pediatric patients. [ 15 22 ] This study intends to investigate the role of ADHD-related clinical findings in ocular traumas in adult population, which to the best of our knowledge has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation